Analisis Pengaruh Sedimentasi terhadap Kapasitas Drainase pada Ruas Glugur Darat II – Pulo Brayan Darat I Kota Medan: Analysis of Sedimentation Effects on Drainage Capacity in the Glugur Darat Area of Medan - Nadya Lamria; Charly Yosep Ardana Silalahi2; Rumilla Harahap; Wisnu Prayogo; Rizky Simanjuntak; Yuni Yolanda (Jurnal Teknologi Lingkungan, 2026)
This study aims to analyze the effect of sedimentation on drainage capacity in the Glugur Darat II to Pulo Brayan Darat I area, Medan City. The main issue addressed is the decline in drainage performance due to sediment accumulation, which potentially causes inundation and flooding, especially in areas with high rainfall intensity. The research method used is field observation through direct measurements at several drainage segments, including channel width, sediment height, water depth, and channel dimensions. Secondary data such as rainfall and population were also used as supporting variables. The results show that sediment height varies across observation segments, with a maximum value reaching 25 cm, significantly reducing the effective capacity of the drainage channel. In addition, high annual rainfall intensity exceeding 3000 mm/year worsens drainage conditions. Sedimentation has been proven to reduce water storage capacity, thereby increasing the risk of inundation. Therefore, routine maintenance and sediment control are necessary to improve drainage system performance.